2014
DOI: 10.1007/s00228-014-1769-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients

Abstract: rs10306114, rs3753380, rs3766355, and rs11568658 single-nucleotide polymorphisms (SNPs) correlate with a response to latanoprost treatment in patients with POAG. These SNPs may be important determinants of variability in response to latanoprost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…The effect of polymorphisms on the response to latanoprost that is used as a treatment for glaucoma has been studied recently. Carriers of a genetic variant of MRP4 (rs11568658) had significantly lower intraocular pressure after latanoprost treatment, indicating that MRP4 efflux affects the absorption of latanoprost [96]. Similarly, an OATP2A1 genetic variant (rs4241366) was found to have some correlation to the intraocular pressure response after topically applied latanoprost in glaucoma patients [97].…”
Section: Accepted Manuscript 6 Pharmacogenetics In Omentioning
confidence: 95%
“…The effect of polymorphisms on the response to latanoprost that is used as a treatment for glaucoma has been studied recently. Carriers of a genetic variant of MRP4 (rs11568658) had significantly lower intraocular pressure after latanoprost treatment, indicating that MRP4 efflux affects the absorption of latanoprost [96]. Similarly, an OATP2A1 genetic variant (rs4241366) was found to have some correlation to the intraocular pressure response after topically applied latanoprost in glaucoma patients [97].…”
Section: Accepted Manuscript 6 Pharmacogenetics In Omentioning
confidence: 95%
“…Moreover, it was shown in the Japanese childhood acute lymphoblastic leukemia (ALL) population that the homozygous variant allele in any of the ABCC4 2269G.A, 912C.A, and 559G.T variants was in correlation with reduced 6-MP dose (Tanaka et al, 2014). More recently, Gao et al (2015) reported that 559G.T was significantly associated with decreased intraocular pressure in response to latanoprost. However, whether these SNPs reduce protein location or expression and impair the binding ability of MRP4 substrates and the mechanism responsible need further investigation.…”
Section: Pharmacogenomics Of Mrp4mentioning
confidence: 99%
“…Meanwhile, the patient's gender correlated with the IOP reduction on day 7, but not on day 30. Sakurai et al 7 and Gao et al 8 found that baseline IOP did not correlate with %ΔIOP. These findings suggest that the key factors related to IOP reduction may be more complicated in patients with high baseline IOP than in patients with low baseline IOP.…”
Section: Discussionmentioning
confidence: 97%
“…However, previous studies showed inconsistent findings between the SNPs of PTGER and the response to latanoprost. 6,8,9 Racial heterogeneity (differences in MAF) may be an important factor responsible for the inconsistency between studies. 5,19 For example, the MAF of rs12093097 (0.114) in this study was lower than that of the NCBI SNP database (0.2376).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation